Une nature arctique qui protège et nourrit : le contre-récit des Kvènes récrit la relation au monde naturel - Viinikka-Kallinen, Anitta (Nordiques, 2020)
The Kvens are a national minority in Norway long subject to a policy of assimilation. This article examines the Kven-language novels of Alf Nilsen-Børsskog as counter-narratives and descriptions of Arctic nature and the Kvens’ living environment. Norwegian fiction has depicted the Kvens since the 1870s, but Nilsen-Børsskog’s series Elämän jatko 1-4 (Life Goes On, 2004-2015) is the first to assume a native perspective to the Kvens’ living environment and experiences. It forms an exceptional counterstory, focusing on the power of the writer’s native background instead of describing a crisis in the minority culture. The descriptions of arctic nature in Life Goes On differ significantly from previous ones, where Arctic it is often depicted as a place of extreme experiences and catastrophes. In addition to nature, the Kvens and Sámi have been subjected to this exoticising description. NilsenBørsskog instead describes the Kvens’ everyday and spiritual life, in which nature and the cultural environment are in harmony and form an important part of Kven identity. Les Kvènes, une minorité nationale de la Norvège, ont longtemps été assujettis à une politique d’assimilation. Cet article analyse les romans en langue kvène d’Alf NilsenBørsskog comme des contre-récits qui accordent un rôle important à la description de la nature et de l’environnement de la vie quotidienne des Kvènes. On trouve des représentations de Kvènes dans la littérature norvégienne depuis les années 1870, mais la série romanesque Elämän jatko (La continuation de la vie, 2004-2015) de NilsenBørsskog est la première œuvre à raconter leurs expériences et leur environnement du point de vue d’un natif. Elle constitue un contre-récit exceptionnel qui place l’origine de l’auteur au point focal au lieu de représenter la crise d’une culture minoritaire. La description de la nature arctique qu’elle donne est sensiblement différente par rapport aux œuvres précédentes où elle est souvent représentée comme une scène d’expériences extrêmes et de catastrophes et les ...